The writing's on the wall for Sherlock. (20th December 2011) - Ruder, Thomas D; Thali, Yannick; Bucher, Matthias; Cottier, Annie; Thali, Michael J; Hatch, Gary M
Abstract : Thomas Ruder and colleagues discover that once again the sleuth's hunches were right